114 Patient Risk Factors for Prolonged Opioid Dependence Following Primary Inflatable Penile Prosthesis Placement Managed with Multimodal Analgesia. Issue 1 (1st April 2022) - Braun, A; Sudhakar, A; Lucas, J; Patel, R; Gross, M; Simhan, J
ABSTRACT: Introduction: Multimodal analgesia (MMA) following inflatable penile prosthesis (IPP) placement has previously demonstrated substantially improved pain control with reduced opioid burden both in the acute and prolonged postoperative period. However, some patients receiving MMA still require opioid pain management beyond the immediate postoperative recovery, placing them at risk for developing prolonged opioid dependence. Objective: In this analysis, we examine patient-specific and perioperative factors predicting increased pain and prolonged use of opioids in the recovery period following primary IPP surgery in those managed with MMA only. Methods: This is a multicenter retrospective review of 165 primary three-piece IPP recipients from 12/2018 to 12/2020 managed with a standardized MMA protocol. Patients on narcotics preoperatively were excluded. Prolonged opioid dependence was defined as active opioid prescriptions in the Prescription Drug Monitoring Program (PDMP) 90 days after surgery in previously opioid-naïve patients. Preoperative, intraoperative and immediate postoperative factors were analyzed to assess correlative risk for increased pain and development of opioid dependence in the MMA cohort. Results: The prolonged opioid use group (2/165) demonstrated substantially higher Visual Analog Scale (VAS) pain scores in PACU (p=0.014) with trends towards higher total morphine equivalents (TME) in PACU (p=0.076). Also seen were higher total morphine equivalents (TME) in postoperative day 0 (p=0.0425), while VAS scores on POD1 (p=0.123) and total TME prescribed at discharge (p=0.646) did not reach statistical significance. In assessing preoperative factors associated with developing opioid-dependence, age (p=0.194), race (p=0.414), BMI (p=0.202) and prevalence of diabetes (p=0.656) and chronic pain (p=0.291) did not demonstrate statistical significance. Intraoperative factors analyzed including operative time (p=0.719), surgical approach (p=1.00), cylinder size (p=0.938), use of rear-tip extenders (p=1.00), reservoir size (p=0.346) and use of drain (p=1.00) also did not yield significance. Conclusions: Patients who developed prolonged postoperative opioid dependence tended to experience higher PACU VAS scores and increased TME requirements throughout their hospitalization. MMA appears to reduce risk of prolonged postoperative opioid dependence in this series. We found no clear preoperative or operative trends for prolonged opioid dependence in MMA patients. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Coloplast